![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(3\cdot5^{x+2}+4\cdot5^{x-3}=19\cdot5^{10}\)
\(\Leftrightarrow5^{x-3}\cdot\left(3\cdot5+4\right)=19\cdot5^{10}\)
\(\Leftrightarrow5^{x-3}\cdot19=19\cdot5^{10}\)
\(\Leftrightarrow5^{x-3}=5^{10}\)
\(\Rightarrow x-3=10\)
\(\Rightarrow x=13\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x-10)^3 = (x-10)^100
=> (x-10)^3 - (x-10)^100 = 0
(x-10)^3. ( 1 - (x-10)^97) = 0
=> (x-10)^3 = 0 => x- 10 = 0 => x = 10
1- (x-10)^97 = 0 => (x-10)^97 = 1 => x - 10 = 1 => x = 11
KL: ...
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\left(-1\right)^{10}+\left(-1\right)^9+\left(-1\right)^8+...+\left(-1\right)^2+\left(-1\right)\)
\(=\left(1-1\right)+\left(1-1\right)+...+\left(1-1\right)\)
=0
b: \(=\left(-1\right)^{100}+\left(-1\right)^{99}+...+\left(-1\right)^2+\left(-1\right)\)
\(=\left(1-1\right)+...+\left(1-1\right)\)
=0
c: \(=1^{100}-1^{99}+1^{98}-1^{97}+...+1^2-1\)
=0
f: \(=3\cdot\sqrt{9-5}+7=3\cdot2+7=13\)
1) 10x−52.2x=22.5x−10210x−52.2x=22.5x−102
⇔102(10x−2+1)=52.22(2x−2+5x−2)⇔102(10x−2+1)=52.22(2x−2+5x−2)
⇔102(10x−2+1)=102(2x−2+5x−2)⇔102(10x−2+1)=102(2x−2+5x−2)
⇔(10x−2+1)=(2x−2+5x−2)⇔(10x−2+1)=(2x−2+5x−2)
⇔(10x−2+1x−2)=(2x−2+5x−2)⇔(10x−2+1x−2)=(2x−2+5x−2)
Để 2 vế bằng nhau ⇔x−2=0⇔x=2
Answer:
\(10^x-25.2^x=4.5^x-100\)
\(⇒(2.5)^x-25.2^x=4.5^x-100\)
\(⇒2^x.5^x-25.2^x=4.5^x-100\)
\(⇒2^x.(5^x-25)=4.(5^x-25)\)
\(⇒2^x.(5^x-25)-4(5^x-25)=0\)
\(⇒(2^x-4)(5^x-25)=0\)
\(\Rightarrow\orbr{\begin{cases}2^x-4=0\\5^x=25\end{cases}\Rightarrow\orbr{\begin{cases}2^x=4\\5^x=5^2\end{cases}}\Rightarrow\orbr{\begin{cases}x=2\\x=2\end{cases}}}\)